2019
DOI: 10.1007/s00217-019-03391-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather conditions on bioactive compound content in sorghum grain

Abstract: Sorghum is the fifth most important cereal in the world in terms of the cropped area. It is mainly grown for feeding animals and it is also used in the food industry. Sorghum grain is generally a rich source of antioxidants such as polyphenols and carotenoids. For this reason, it is considered as a good source of bioactive food components and it has health-promoting properties. Sorghum is a gluten-free cereal grown in many regions worldwide, primarily in the tropical and subtropical regions. However, new hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 61 publications
(83 reference statements)
1
25
0
Order By: Relevance
“…John et al [ 95 ] observed the presence of large amounts of carotenoids, phenolic acids, flavonoids, and tannins [ 8 , 96 , 97 ] in sorghum accessions, contributing to antioxidant activity. Moreover, in a similar study, high concentrations of phenolic acids, flavonoids, and carotenoids in sorghum grains were observed [ 85 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…John et al [ 95 ] observed the presence of large amounts of carotenoids, phenolic acids, flavonoids, and tannins [ 8 , 96 , 97 ] in sorghum accessions, contributing to antioxidant activity. Moreover, in a similar study, high concentrations of phenolic acids, flavonoids, and carotenoids in sorghum grains were observed [ 85 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 73%
“…In another study, the irradiance period of the growing sorghum genotypes influenced the phenolic content and antioxidant activity of sorghum plants [ 82 , 83 , 84 ]. Similarly, Przybylska-Balcerek et al [ 85 ] observed variations in antioxidant activity and phenolic compound accumulation due to differences in the air temperature and precipitation rate during sorghum growth. In this study, since the environmental conditions experienced by the accessions were the same, variations in their TPC and TFC could be attributed to the genetic variation of individual sorghum accessions.…”
Section: Discussionmentioning
confidence: 97%
“…Such results suggest that flavonoid production could be influenced by environmental conditions, as we have also noted for FC contents. Numerous studies have been published about the influence of environmental factors on the biosynthesis of flavonoids ( Jaakola and Hohtola, 2010 ; Wu et al, 2019 ; Morales et al, 2020 ; Przybylska-Balcerek et al, 2020 ; Morales et al, 2021 ). Jaakola and Hohtola (2010) indicated the effect of high or low temperature on the composition or concentrations of flavonoids in many plant species.…”
Section: Resultsmentioning
confidence: 99%
“…However, environmental factors as temperature, and light as well as fertilization of the soil play a key role in the richness of bioactive compounds in different cultivars as well as fruit ripeness [3][4][5]. Piscitelli et al [6] focused on San Marzano Cirio 3 and Pomodoro Giallo cultivars while studying the antioxidant and antitumoral properties of nine different cultivars of tomatoes.…”
Section: Introductionmentioning
confidence: 99%